A new data acquisition system for Schottky signals in atomic physics experiments at GSI's and FAIR's storage rings - Trageser, Christian; Brandau, C.; Kozhuharov, C.; Litvinov, Yuri A.; Müller, A.; Nolden, Fritz; Sanjari, Mohammad Shahab; Stöhlker, Thomas (Physica scripta, 2015)
A new continuous and broadband data acquisition system for measurements of Schottky-signals of ions revolving in a storage ring has been implemented. This set-up is capable of recording the radio frequency (RF) signal of the ions that circulate in the storage ring with a sustained acquisition rate of more than IQ-samples per second. This allows several harmonics of the full momentum acceptance of a storage ring to be measured at the same time. The RF signal analyzer modules are complemented by further electronic modules such as counters, precision clocks and synchronization modules that facilitate a seamless integration with main experimental data acquisitions for atomic and nuclear physics. In this contribution, the setup and first results from a test run at the experimental storage ring at GSI, Darmstadt, Germany, are presented.
Gesehen am 06.07.2020